Financial stability policies and bank lending: Quasi-experimental evidence from Federal Reserve interventions in 1920-21 - Kilian Rieder (European Systemic Risk Board (ESRB), European System of Financial Supervision, 2020)
I estimate the comparative causal effects of monetary policy "leaning against the wind" (LAW) and macroprudential policy on bank-level lending and leverage by drawing on a single natural experiment. In 1920, when U.S. monetary policy was still decentralized, four Federal Reserve Banks implemented a conventional rate hike to address financial stability concerns. Another four Reserve Banks resorted to macroprudential policy with the same goal. Using sharp geographic regression discontinuities, I exploit the resulting policy borders with the remaining four Federal Reserve districts which did not change policy stance. Macroprudential policy caused both bank-level lending and leverage to fall significantly (by 11%-14%), whereas LAW had only weak and, in some areas, even perverse effects on these bank-level outcomes. I show that the macroprudential tool reined in over-extended banks more effectively than LAW because it allowed Federal Reserve Banks to use price discrimination when lending to highly leveraged counterparties. The perverse effects of the rate hike in some areas ensued because LAW lifted a pre-existing credit supply friction by incentivizing regulatory arbitrage. My results highlight the importance of context, design and financial infrastructure for the effectiveness of financial stability policies.
Keywords: E44; E51; E52; E58; G21; N12; N22; 330; monetary policy; macroprudential policy; leaning against the wind; progressive discount rate; creditboom; bank lending; leverage; financial crisis; Federal Reserve System; recession of 1920/1921